(3GSJjYGH GdhLhg GdeecfI aj UfYI GdGSWQdGHs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg aEfg GjOg Gddg CeQfi Cf CKHg dg UfYJg HGdWQb GdUfGYjI s
(3BNQgG (B:s
(3hjchf CMSf ai GdUhQI Hd dh KefJ GdUaMI HCbWGH HOd GdQHjY (B,(3bGQHJ Cf JYe GdYQhV ai GdYed s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(150) s
Keywords: (3Gdadcs